Body Size Influences Stingless Bee (Hymenoptera: Apidae) Communities Across a Range of Deforestation Levels in Rondônia, Brazil. Issue 2 (19th April 2019) - Mayes, D M; Bhatta, C P; Shi, D; Brown, J C; Smith, D R
Abstract: Developments in understanding bee responses to habitat loss indicate that body size is a trait with important consequences for conservation. Stingless bees (Hymenoptera, Apidae, Meliponini) are a diverse group of eusocial bees providing pollination services in tropical landscapes, exhibiting a large range in body size across species. We tested the effects of deforestation on the body sizes of stingless bee communities by using museum specimens and revisiting a previous effort that sampled stingless bee communities across varying levels of deforestation at 183 sites in Rondônia, Brazil, in 1996–1997. Body size measurements (intertegular distance) from 72 species collected were included as dependent variables in response to forest area, forest edge, and connectivity of forest patches at several spatial scales. We find that stingless bee body size is negatively related to forest cover: mean community body size was larger in areas with greater amounts of deforestation, and smaller in areas with less deforestation. Second, stingless bee species richness was positively associated with forest edge regardless of body size. Lastly, we find that as forest patch isolation increased, the stingless bee community body size also increased. These findings support hypotheses that small stingless bee species might be more negatively affected by deforestation, adding to the growing body of evidence that stingless bees require areas of intact forest in near proximity to other forest patches to conserve these diverse pollinator communities.